PROTOLITHS OF THE METAMORPHIC ROCKS OF THE FEDOROV COMPLEX, ALDAN SHIELD: CHARACTER, AGE, AND GEODYNAMIC ENVIRONMENTS OF ORIGIN - Velikoslavinsky S.D.; Kotov A.B.; Sal'nikova E.B.; Kovach V.P.; Glebovitsky V.A.; Zagornaya N.Yu.; Yakovleva S.Z.; Anisimova I.V.; Fedoseenko A.M.; Tolmacheva E.V. (My University, 2006)
Geochemical data indicate that the protoliths of the overwhelming majority of the metamorphic rocks composing the Fedorov Complex in the Aldan granulite megacomplex were volcanic rocks of three groups, which occur in different proportions in the complex: (i) volumetrically predominant (no less than 90%) continuous differentiated island-arc basalt-andesite-dacite-rhyolite series, (ii) within-plate basalts, whose composition was similar to that of low-Ti traps, and (iii) basalts of composition similar to that of continentalrift basalts. The U-Pb zircon crystallization age of the metamorphosed basaltic andesites of the Fedorov Complex was estimated at 2006 ± 3 Ma, which testifies, when considered together with preexisting geochronological data, that the complex was produced during a time span of no longer than 25 m.y. A model is proposed according to which the complex was produced within the geodynamic system of the active continental margin of the Olekma-Aldan continental microplate and the Fedorov island arc. © Pleiades Publishing, Inc., 2006.